Developing an instrument for measuring the faith of the students of Islamic senior high school - Shodiq Shodiq; Zamroni Zamroni; Kumaidi Kumaidi (REID (Research and Evaluation in Education), 2016)
The study aims to develop an instrument used to measure  faith of the students of Islamic senior high schools. The study was a research and development study consisting of three steps: pre development, development process, and presentation. The quantitative data analysis was to test the validity and reliability of the instrument and to test the model fit through the Confirmatory Factor Analysis (CFA) using LISREL 8.80 Program. The results of the study show that: (1) the faith instrument of the study is an inventory model of summated rating scale containing 113 items named as Islamic Faith Scale; (2) the instrument validity is considered as the loading factor value (the lowest loading factor value is 0.47 and the highest is 0.89). The instrument reliability regarded as the coefficient of the construct reliability is 0.7, (the coefficient of reliability construct of tashdiq al-qalb is 0.847, and the coefficient of the construct reliability of amal al-qalb is 0.999); (3) the overall model fit produces a fit model indicated by Chi Square (χ2) = 48.23, df = 64, p-value = 0.929 (p 0.05), and Root Mean Square Error of Approximation = 0.000 ( 0.08).